Kesejahteraan psikologis guru non-Pegawai Negeri Sipil (PNS): Menguji peranan relisiensi dan kebersyukuran - Ismawati; Suroso; Muhammad Farid; Niken Titi Pratitis (INNER: Journal of Psychological Research, 2022)
Abstract The phenomenon of the teacher whosued forprofessional as educator regardless of status or suitability of rewards tends to make non-civil servant teachers to burdened and difficult to develop positive aspects of themselves. This leads to low psychological well-being. Psychological well-being can be improved through resilience and gratitude. This research aims to examine the correlation between resilience and gratitude with psychological well-being.. Respondents consist of 80 Non-civil teachers in disadvantaged areas. Collecting data using a Likert scale. Data were analyzed by regression test using SPSS version 18 for Windows with good results shows that: 1) refficiency and gratitude correlated with psychological well-being. 2) resilience is positively correlated with psychological well-being. 3) Gratitude is positively correlated with psychological well-being. So, the higher the resilience and gratitude, the higher the psychological well-being. Keywords: Gratitude, Psychological well-being, Resilience